Germinação e vigor de sementes de Magonia Pubescens a. St.-Hil. armazenadas em diferentes embalagens, com e sem pré-embebição em água e, formação de plântulas em diferentes recipientes - Arantes, Cárita Rodrigues de Aquino (2015)
Timbo (M. pubescens) is a specie with ornamental potential, that can be used in gardens and squares composition, and mainly, for street afforestation; it is also suitable for planting in degraded areas of permanent preservation. The objectives in this study were, in addition to determining the biometric aspects of fruits and seeds, check the effect of seed size, storage, packaging and soaking time on germination and seed vigor, and the container in formation of timbo seedlings. The fruits were collected in Cuiabá city, Mato Grosso, and taken to the Seeds Laboratory of the Mato Grosso Federal University to fruits and seeds mensuration of mass and dimensions. In laboratory experiment the design was completely randomized in a split plot scheme in time, being allocated in the main plots: seed size (large and small); packaging (transparent polyethylene with a thickness of 0.5 mm and kraft paper bag) and water soaking time (0, 12 and 24 hours) and in the subplots, the storage time (0, 3, 6, 9 and 12 months), with five replications of ten seeds. The experiment in seedling production nursery has been installed according to completely randomized design in a factorial 2x2x3 (two seedlings production containers, two seed sizes, and three times of seeds soaking in water) with four replications of six containers with one seed each, totaling 12 treatments and 48 experimental units. The seeds soaking did not affect the final percentage of germination, but accelerated the process reducing the average time of germination, this favored the seedlings formation, which are more vigorous when compared to seedlings formed from seeds that have not been soaked before sowing.